ASYKALU AL-TASYBIH FI AL-SYI’RI KITAB TA’LIM MUTA’ALIM LI AL-SYAIKH AL-IMAM BURHANUDDIN AL-ZARNUZI: Bentuk Tasybih dalam Syiir Pada Kitab Ta'lim Mutaallim Karya Syeh Imam Burhanuddin Al Zarnuzi - Riyadi, Agus; Aulia, Sulthon; Puadah, Sri Samrotul; Rizqi , Anggi Maulana (Jazirah: Jurnal Peradaban dan Kebudayaan, 2024)
The Book of Ta’lim Muta’alim is one of the most important books of the Islamic heritage that has been studied by the student of knowledge in the world, and in which he searches for methods of teaching and learning. In this book there are accurate values ​​for the teacher and the learner through the poetry that the author wrote, as well as the poetry that the author quoted from ancient scholars and poets to advise readers, but it is still difficult to understand the content of the poetry due to the large number of methods of similes, metaphors, and metonymies. This research came to demonstrate the application of the science of rhetoric in the poetry of the book Teaching the learner by Sheikh Imam Burhan al-Din al-Zarnuji and to help readers understand his poetry. This research is descriptive qualitative research, and the researcher collected data in this research using the library method. The researcher used the graphical analytical method to analyze the data in this research. One of the most important results of this research is that the number of poetries in the learner’s education book, which includes the application of rhetoric, is 30, including similes. It became clear from this that simile in rhetoric has an important role in facilitating the readers’ understanding of poetry.